The Role of Cyber Expertise and Other Types of Examinations in Solving Cybercrime Cases - Anorboyev Amiriddin Ulug‘bek o‘g‘li (Multicore International Journal of Multidisciplinary (MIJM), 2026)
The rapid development of information and communication technologies has significantly increased both the number and complexity of cybercrime cases. These crimes often involve sophisticated technical processes that exceed the professional competence of investigators, prosecutors, and judges who are primarily trained in legal sciences. As a result, the effectiveness of cybercrime investigations largely depends on the proper use of expert examinations based on specialized technical knowledge. This study aims to analyze the role and significance of cyber expertise in solving cybercrime cases, identify the shortcomings of existing computer-technical (digital forensic) expertise, and justify the need for a more comprehensive and specialized classification of expertise in the field of information and communication technologies. The research employs doctrinal legal analysis, comparative analysis, and a descriptive-analytical method. National legislation of the Republic of Uzbekistan, law enforcement and judicial practice, and foreign experience in the application of cyber and digital forensic expertise were examined, alongside technical aspects of telecommunication networks, information systems, software, cryptography, and communication quality. The findings demonstrate that the prevailing reliance on computer-technical expertise is insufficient to address the multifaceted nature of cybercrimes, which frequently involve telecommunication infrastructure, encryption technologies, software applications, and communication quality issues beyond the traditional scope of digital forensics. The study substantiates the need to introduce specialized types of expertise, including telecommunication network and infrastructure expertise, information systems and computer data expertise, software and application expertise, cryptographic expertise, communication coverage and quality expertise, and cyber forensic auditing. Particular emphasis is placed on cyber forensic auditing as a mechanism for ensuring the admissibility and reliability of digital evidence. The study concludes that the current forensic framework should be expanded and systematized, and recommends developing specialized expert training and updating procedural legislation to enhance the effectiveness of cybercrime investigations.